2021
DOI: 10.1101/2021.05.26.445878
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effective prophylaxis of COVID-19 in rhesus macaques using a combination of two parentally-administered SARS-CoV-2 neutralizing antibodies

Abstract: SARS-CoV-2 is a respiratory borne pathogenic beta coronavirus that is the source of a worldwide pandemic and the cause of multiple pathologies in man. The rhesus macaque model of COVID-19 was utilized to test the added benefit of combinatory parenteral administration of two high-affinity anti-SARS-CoV-2 monoclonal antibodies (mAbs; C144-LS and C135-LS) expressly developed to neutralize the virus and modified to extend their pharmacokinetics. After completion of kinetics study of mAbs in the primate, combina… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…SARS-CoV-2 infection in the non-human primate (NHP), rhesus macaques ( Macaca mulatta ), recapitulates mild to moderate human disease 1618 . Infected macaques exhibit viral shedding through the respiratory tract and viral pneumonia similar to the mild form seen in humans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SARS-CoV-2 infection in the non-human primate (NHP), rhesus macaques ( Macaca mulatta ), recapitulates mild to moderate human disease 1618 . Infected macaques exhibit viral shedding through the respiratory tract and viral pneumonia similar to the mild form seen in humans.…”
Section: Introductionmentioning
confidence: 99%
“…To gain critical insights into systemic infection by SARS-CoV-2, new animal models are needed to determine the extent of disseminated infection and its relationship to pathogenesis. SARS-CoV-2 infection in the non-human primate (NHP), rhesus macaques (Macaca mulatta), recapitulates mild to moderate human disease [16][17][18] . Infected macaques exhibit viral shedding through the respiratory tract and viral pneumonia similar to the mild form seen in humans.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of different modes of vaccine delivery on immune efficacy have also been verified in animal models. In addition to traditional intramuscular injection, oral (Beddingfield et al, 2021;Langel et al, 2022;Yu et al, 2022b) and intranasal vaccines (Langel et al, 2022;Sui et al, 2021b;Tokunoh et al, 2023) have also been shown to provide protection. These animal models have significantly enhanced our understanding of the immune protective mechanisms against SARS-CoV-2 (Figure 2).…”
Section: Immune Protection Against Sars-cov-2mentioning
confidence: 99%
“…Viral RNA Quantification by Quantitative Real-Time PCR Quantification of viral RNA was performed as described22 using the CDC N1 primers/probe for quantification of total viral RNA and with primers/probe specific for the nucleocapsid subgenomic RNA to provide an estimate of replicating virus. Specifically, vRNA was quantified using the QuantStudio 6 Real-Time PCR System (Applied Biosystems, Waltham, MA).…”
mentioning
confidence: 99%